Hyperthermia treatment planning guided applicator selection for sub-superficial head and neck tumors heating. (18th August 2018) - Drizdal, Tomas; Paulides, Margarethus M.; van Holthe, Netteke; van Rhoon, Gerard C.
Abstract: Purpose: In this study, we investigated the differences in hyperthermia treatment (HT) quality between treatments applied with different hyperthermia systems for sub-superficial tumours in the head and neck (H&N) region. Materials and methods: In 24 patients, with a clinical target volume (CTV) extending up to 6 cm from the surface, we retrospectively analysed the predicted HT quality achievable by two planar applicator arrays or one phased-array hyperthermia system. Hereto, we calculated and compared the specific absorption rate (SAR) and temperature distribution coverage of the CTV and gross tumour volume (GTV) for the Lucite cone applicator (LCA: planar), current sheet applicator (CSA: planar) and the HYPERcollar (phased-array). Results: The HYPERcollar provides better SAR coverage than planar applicators if the target region is fully enclosed by its applicator frame. For targets extending outside the HYPERcollar frame, sufficient SAR coverage (25% target coverage, i.e. TC25 ≥ 75%) can still be achieved using the LCA when the target is fully under the LCA aperture and not deeper than 50 mm from the patient surface. Conclusion: Simulations predict that the HYPERcollar (hence also its successor the HYPERcollar3D) is to be preferred over planar applicators such as LCA and current sheet applicator in sub-superficial tumours in the H&N region when used within specifications.